1996
DOI: 10.1111/j.1432-1033.1996.00978.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Expression System on Chromophore Binding and Preservation of Spectral Properties in Recombinant Phytochrome A

Abstract: N-Terminal deletion mutants of the plant photoreceptor phytochrome, additionally truncated at two different positions at their C-terminal ends, were expressed both in Escherichia coli and in yeast (Pichia pastoris) and converted into chromoproteins upon chromophore incorporation. The start and end positions of the cDNA employed (phyA from oat) mimic the positions of tryptic cleavage (deletion of the first 64 amino acids, and stop codons after amino acid positions 425 or 595, generating 39-kDa and 59-kDa peptid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 24 publications
1
38
0
Order By: Relevance
“…Several groups have reported in vitro assembly of PhyB and have shown that it has similar spectral properties to PhyA. [134][135][136] To analyze the structural requirements of the chromophore for the spectral properties of PhyB, we designed and chemically synthesized more than 20 bilin chromophore derivatives (Fig. 10), including natural PÈB and PCB, and reconstituted them with recombinant Arabidopsis PhyB apoprotein (PHYB) through collaborative study with biologists.…”
Section: Assembly Of the Synthetic Bilin Chromophoresmentioning
confidence: 99%
See 1 more Smart Citation
“…Several groups have reported in vitro assembly of PhyB and have shown that it has similar spectral properties to PhyA. [134][135][136] To analyze the structural requirements of the chromophore for the spectral properties of PhyB, we designed and chemically synthesized more than 20 bilin chromophore derivatives (Fig. 10), including natural PÈB and PCB, and reconstituted them with recombinant Arabidopsis PhyB apoprotein (PHYB) through collaborative study with biologists.…”
Section: Assembly Of the Synthetic Bilin Chromophoresmentioning
confidence: 99%
“…Finally, the deprotection of the allyl ester moiety of 134 was achieved by Pd 0 -catalyzed reaction 47,49 using sodium p-toluenesulfinate as a nucleophile in THF/MeOH to give the desired locked chromophore 122 (15Za-18Et-BV) in 90% yield. 54,115 2.10.3 Synthesis of the E-syn CD-Ring Component and 15Es-18Et-BV: 5-Tosylpyrrolinone derivative 114 was prepared starting from propenal (135) as shown in Scheme 32. Treatment of 135 with acetic acid in the presence of a catalytic amount of zinc acetate afforded 3-acetoxypropanal (136) in 40% yield.…”
mentioning
confidence: 99%
“…In contrast, PhyB has not been well characterized because of its low abundance in native tissue. Recently, several groups reported in vitro assembly of PhyB and showed that it has similar spectral properties to PhyA (35)(36)(37).…”
mentioning
confidence: 99%
“…The image shows the thioether linkage that connects the chromophore to the Cys at amino acid position -320 (322 of oat region was sufficient for photosensory function (Lagarias and Rapoport, 1980;Boylan et al, 1994). Transgenic plant and recombinant expression experiments have refined these original conclusions and established that the 40-kD region flanking Cys-322 is sufficient for chromophore attachment and photoreversibility (Cherry et al, 1993;Gartner et al, 1996). This work also showed that there is a blue shift of the Pfr absorption maximum and increased nonphotochemical reversion of Pfr to Pr when a 6-to 10-kD region at the N terminus is removed, suggesting that this region may be involved in establishing the proper chromophore-protein environment (Cherry et al, 1992).…”
Section: (B)mentioning
confidence: 99%
“…Two types of studies have been performed on the photochemically active N-termina1 chromophore binding domain-overexpression in transgenic plants, and in vitro assembly of truncated or mutant recombinant phytochromes in yeast (Deforce et ai., 1991 ;Wahleithner et al, 1991 ;Cherry et al, 1993;Kunkel et al, 1993;Hill et al, 1994;Gartner et al, 1996). Earlier studies had established that Cys-322 of oat PHYA was responsible for chromophore binding and that the 70-kD N-terminal (A) The two spectrally photointerconvertible forms of phytochrome, Pr and Pfr.…”
Section: Phytochrome Structurementioning
confidence: 99%